A Comparative Study of Various Extraction Techniques for Extracting Antioxidant-Rich Phytoconstituents from Eryngium foetidum Leaves Utilizing Spectrophotometric and HPLC Applications - Shanthirasekaram Kokilananthan; Bulugahapitiya, Vajira P; Manawadu, Harshi; Gangabadage, Chinthaka Sanath (Malaysian Journal of Science, 2025)
Eryngium foetidum L. (Apiaceae) is known to possess many healthcare properties and has been used in the traditional system of medicine for various health issues. Despite that less scientific data on its photochemistry and antioxidant properties is limited. Therefore, this study aimed to document the photochemistry and antioxidant properties of leaves by following different extraction techniques to extract the plant constituents. Sonication (EN1), Soxhlet (EN2), maceration (EN3), and maceration with heat (EN4) were used as the extraction techniques while water was used as the extracting solvent. The HPLC method with a PDA detector was developed to compare the phytochemicals profile under each technique. The antioxidant capacities and content of saponins (SC), terpenoids (TC), flavonoids (TFC), tannins (TTC), alkaloids (AC), and polyphenolics (TPC) were determined spectrophotometrically. The EN2 and EN4 methods were identified using the HPLC-PDA application as yielding the highest overall results and giving a wide range of phytochemicals. The quantitative analyses resulted in high SC, TTC, TC, and TPC in the EN4 extraction process (185.84±0.54 mg SE/g, 36.99±0.64 mg TAE/g, 0.89±0.01 mM LE/g, and 37.37±0.65 mg GAE/g, respectively) and low in the EN1. TFC levels in EN2 were high (11.84±0.14 mg QE/g), whereas it was low in EN3. Furthermore, AC was higher in the extraction method EN3 (1.67±0.01 mg AE/g) and lower in the extraction technique EN2. The total antioxidant capacity was higher in the EN4 extract (47.17±0.20 mg Trolox Eq/g) and lower in the EN1 extract. The lowest IC50 in the 2,2′-Diphenyl-1-Picrylhydrazyl (DPPH) assay was noted for EN3 extract (12.91±0.02 mg/mL) revealing the highest scavenging activity than the other extracts. Based on HPLC and spectrophotometric analyses, maceration with heat (EN4) is recommended for efficiently extracting polyphenols and antioxidants from E. foetidum leaves. The application of heat would also improve the extraction efficiency of phytochemicals.